Implementation of Digital Transformation and Employee Work Efficiency in Hospitals - Ida Ayu Galih Pertiwi; Dasrun Hidayat; Mira Veranita (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
Abstract This study aims to analyze the effect of digital transformation on employee work efficiency, and to explain the mechanisms linking this variable within the hospital’s operational context. The study uses a mixed-method approach with a sequential explanatory design, beginning with a quantitative phase through an employee questionnaire survey, followed by a qualitative phase through in-depth interviews to clarify and enrich the quantitative findings. Conceptually, the model is built on the integration of the Technology Acceptance Model (TAM) and the Resource-Based View (RBV), which position digital transformation as a strategic resource that influences work efficiency at the individual level. Quantitative data were analyzed using multiple linear regression with classical assumption tests, while qualitative data were analyzed thematically. The results show that digital transformation has a positive and significant effect on work efficiency through improved workflows, use of information systems, and reduced time wastage, highlighting the need for continuous investment in the integration of technology-based work processes in hospitals.